Progress in the preparation of an active immunization model of anti-N-methyl-D-aspartate receptor encephalitis in animals - Zeng, Kuikui; Liu, Yuting; Yang, Sai; Liu, Lingjuan (Frontiers in Immunology, 2025)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is the most common form of autoimmune encephalitis, and its primary immunologic mechanism is that NMDA antibodies bind to the NMDA receptor, causing NMDAR to internalize and weaken to trigger autoimmune encephalitis. Currently, NMDAR antibodies are detected in the cerebrospinal fluid of patients with NMDAR encephalitis, which is associated with autoantibodies against neurosurface or synaptic antigens, and this antibody is an important marker for clinical diagnosis. However, both the complete pathogenesis and the pathophysiological mechanisms of anti-NMDAR encephalitis remain poorly understood. Animal models have been established as a fundamental research strategy to elucidate the underlying mechanisms of this disease. Among these animal models, active immunity models have attracted significant attention due to its superior ability to recapitulate the disease onset and progression. Active immunity models of NMDAR encephalitis contain several classifications, each of which has its specific strengths and scope of applicability, depending on the research objectives. The primary objective of this review is to systematically classify existing active immunization models of anti-NMDAR encephalitis, with detailed discussion on their establishment protocols, respective advantages, current applications, and future prospects. This comprehensive analysis aims to provide valuable references and guidance for future basic research and clinical investigations on NMDAR encephalitis.